2007
DOI: 10.1681/asn.2006080895
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Nephropathy Is Associated with Oxidative Stress and Decreased Renal Nitric Oxide Production

Abstract: The pathogenesis of diabetic nephropathy remains far from clear, partly due to the lack of a suitable animal model that mimics human renal disease in type 2 diabetes. In this study, the natural history of renal manifestations in ZSF 1 rats, a recently developed rodent model of type 2 diabetes, is described. Male ZSF 1 rats developed obesity and hyperglycemia by 20 weeks of age on a highcarbohydrate diet. They also developed systolic and diastolic hypertension, hypercholesterolemia, profound hypertriglyceridemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
144
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(159 citation statements)
references
References 30 publications
(28 reference statements)
11
144
1
Order By: Relevance
“…Jointly, it is possible that hypoinsulinemia during long term diabetes downregulates LPL and activates the HMG-COA reductase pathway and might play a role in excessive lipid accumulation during early stages of diabetic nephropathy. The strong correlation between diabetic-endothelial dysfunction and nephropathy has been demonstrated in various studies [5,38,39] . Worthy of note is that increased concentrations of free fatty acids impairs NO production by downregulating eNOS and decreases endothelial dependent vasodilation [40,41] .…”
Section: Of Nephropathymentioning
confidence: 78%
“…Jointly, it is possible that hypoinsulinemia during long term diabetes downregulates LPL and activates the HMG-COA reductase pathway and might play a role in excessive lipid accumulation during early stages of diabetic nephropathy. The strong correlation between diabetic-endothelial dysfunction and nephropathy has been demonstrated in various studies [5,38,39] . Worthy of note is that increased concentrations of free fatty acids impairs NO production by downregulating eNOS and decreases endothelial dependent vasodilation [40,41] .…”
Section: Of Nephropathymentioning
confidence: 78%
“…Indeed, NO may be extremely important for renoprotection in the diabetic state. Recent experimental studies of diabetic rats and mice have indicated that decreased renal NO levels are associated with the development of renal histologic lesions 31 and that NO deficiency by endothelial NO synthase knockout causes glomerular endothelial injury and overt albuminuria. 32 The reduction of circulating NO in the microalbuminuric stage of DN observed in the present study was probably attributed to the direct scavenging of NO by excessive superoxide, because serum NT levels, which reflect the formation of peroxynitrite by chemical interaction of superoxide with NO, were enhanced in this stage.…”
Section: Discussionmentioning
confidence: 99%
“…The nephropathy associated with diabetes has been attributed to oxidative stress [2]. Oxidative stress can be caused either by the increased production of reactive oxygen species (ROS) or a deficiency in antioxidant defense.…”
Section: Introductionmentioning
confidence: 99%